THEOLOGI FUNDAMENTALISME - Abu Bakar (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2009)
Fundamentalism does not just show up, because fundamentalism is a phenomenon that always appears in every religion and belief which represents a rebellion against moderniry. Indeed only a small partial fundamentalists who peiform acts of terrorism, but its impact is global For groups. for groups who do not like the violence come to enjoy as a result of a handful of Islamic groups called fanatics or radicals. Islamic fundamentalism is one of the new phenomenon in world politics. Western world has experienced a failure in managing world politics, so they try to replace the new world order based on the political interpretation of Islam by thinker